Lateral Spacing of TiO2 Nanotube Coatings Modulates In Vivo Early New Bone Formation - Negrescu, Andreea Mariana; Ionascu, Iuliana; Necula, Madalina Georgiana; Tudor, Niculae; Kamaleev, Maksim; Zarnescu, Otilia; Mazare, Anca Valentina; Schmuki, Patrik; Cimpean, Anisoara (Biomimetics, 2025)
Due to the bio-inert nature of titanium (Ti) and subsequent accompanying chronic inflammatory response, an implant’s stability and function can be significantly affected, which is why various surface modifications have been employed, including the deposition of titanium oxide (TiO2) nanotubes (TNTs) onto the native surface through the anodic oxidation method. While the influence of nanotube diameter on cell behaviour and osteogenesis is very well documented, information regarding the effects of nanotube lateral spacing on the in vivo new bone formation process is insufficient and hard to find. Considering this, the present study’s aim was to evaluate the mechanical properties and the osteogenic ability of two types of TNTs-based pins with different lateral spacing, e.g., 25 nm (TNTs) and 92 nm (spTNTs). The mechanical properties of the TNT-coated implants were characterised from a morphological point of view (tube diameter, spacing, and tube length) using scanning electron microscopy (SEM). In addition, the chemical composition of the implants was evaluated using X-ray photoelectron spectroscopy, while surface roughness and topography were characterised using atomic force microscopy (AFM). Finally, the implants’ hardness and elastic modulus were investigated using nanoindentation measurements. The in vivo new bone formation was histologically evaluated (haematoxylin and eosin—HE staining) at 6 and 30 days post-implantation in a rat model. Mechanical characterisation revealed that the two morphologies presented a similar chemical composition and mechanical strength, but, in terms of surface roughness, the spTNTs exhibited a higher average roughness. The microscopic examination at 1 month post-implantation revealed that spTNTs pins (57.21 ± 34.93) were capable of promoting early new bone tissue formation to a greater extent than the TNTs-coated implants (24.37 ± 6.5), with a difference in the average thickness of the newly formed bone tissue of 32.84 µm, thus highlighting the importance of this parameter when designing future dental/orthopaedic implants.
CRIS-Team Scopus Importer:2025-03-14
Keywords: in vivo new bone formation; intertube spacing; nanotopographic surfaces; osteoblasts; TiO